2023
DOI: 10.1002/ange.202304007
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Synthesis of Essential Amino Acids from Nitric Oxide Using Atomically Dispersed Fe on N‐doped Carbon

Abstract: How to transfer industrial exhaust gases of nitrogen oxides into high‐values product is significantly important and challenging. Herein, we demonstrate an innovative method for artificial synthesis of essential α‐amino acids from nitric oxide (NO) by reacting with α‐keto acids through electrocatalytic process with atomically dispersed Fe supported on N‐doped carbon matrix (AD‐Fe/NC) as the catalyst. A yield of valine with 32.1 μmol mgcat−1 is delivered at −0.6 V vs. reversible hydrogen electrode, corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…18,19 On the other hand, the key processes of glyoxylic acid formation and oxime hydrogenation suffer from poor selectivity and sluggish rate (Figure 1A). 20 Therefore, this puts high demands on the electrocatalyst design to have the capability to effectively convert the reactants and intermediates, 22 which might feed back to the high rate and selectivity for glycine formation (Figure 1B). In light of this, we consider designing stable dual-site metal catalysts to match the multistep reaction pathways in glycine formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 On the other hand, the key processes of glyoxylic acid formation and oxime hydrogenation suffer from poor selectivity and sluggish rate (Figure 1A). 20 Therefore, this puts high demands on the electrocatalyst design to have the capability to effectively convert the reactants and intermediates, 22 which might feed back to the high rate and selectivity for glycine formation (Figure 1B). In light of this, we consider designing stable dual-site metal catalysts to match the multistep reaction pathways in glycine formation.…”
mentioning
confidence: 99%
“…These advances prompt us to consider whether electrocatalysis can be used to synthesize the value-added amino acid product. Fortunately, some studies have initially shown the possibility of synthesizing glycine from carbon and nitrogen monomers such as keto acids, oxalic acid, hydroxylamine, and nitrate. However, it is urgent to simultaneously achieve the high selectivity (>60%) and high current density (>100 mA cm –2 ) for the industrially relevant requirements. In particular, using widely accessible chemicals as reaction monomers is expected to expand the scope of resource utilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation